Cable TV: Bringing Home Native Speaker to Increase Listening Comprehension of the Students of English Education Department Teacher Training and Education Faculty Muria Kudus University - Rismiyanto Nuraeningsih (IAIN Salatiga, 2011)
This study investigated the use of cable TV to increase listening comprehension of the students of English education department of Muria Kudus University. The aims were to find out: (1) the listening comprehension achievement of the students taught by using cable TV, (2) the students’ response towards the teaching of listening comprehension class by using cable TV, and (3) the students’ difficulties when being involved in the listening class taught by using cable TV are. A classroom action research was conducted with three cycles. The data was collected by using test, observation checklist, a questionnaire. The subject consisted of 29 students joining Advanced Listening class. The findings show that: (a) The listening comprehension achievement of the students taught by using cable TV in cycle I, II, III is fair, (b) The students have enthusiasm and seriousness and motivation in joining the class in all cycles, (c) In cycle III the students’ difficulties when being involved in the listening comprehension class taught by using cable TV are more and more decreasing. Keywords: Cable TV, Listening ComprehensionKeywords;Cable TV; Listening Comprehension